Analisis Nilai Edukatif dalam Novel Dear, Imamku Karya Mellyana Dhian - Suci Ulandari; Iba Harliyana; Maulidawati Maulidawati (Jurnal Dedikasi Pendidikan, 2023)
This research is entitled "Analysis of Educational Values in the Novel Dear, Imamku by Mellyana Dhian". The formulation of the problem in this research is how the educational values are contained in the novel Dear, Imamku by Mellyana Dhian and what the meanings of the educational valuescontained in the novel Dear, Imamku by Mellyana Dhian. This research method uses a descriptive method with a qualitative approach. Data collection techniques used in this study were reading and note-taking techniques. The data analysis technique in this study uses flow analysis techniques which include three components, namely data reduction, data presentation, and drawing conclusions. The data in this study are excerpts from sentences, dialogues, and discourses that contain the educational value in the novel Dear, Imamku by Mellyana Dhian. While the data source is the novel Dear, Imamku by Mellyana Dhian, totaling 302 pages published by Andalusia, the first printing in July 2018. Based on the results of research and discussions that have been carried out on the educational value contained in the novel Dear, Imamku by Mellyana Dhian, it can be concluded that there are educational values in the novel Dear, Imamku by Mellyana Dhian, including 28 religious values, 2 cultural values, 18 social values, and 14 moral values.